2010
DOI: 10.1002/adem.200980072
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Resorbable Calcium Phosphate Ceramic for Bone Implants and Local Alendronate Delivery

Abstract: A novel biphasic calcium phosphate ceramic composed of tricalcium phosphate (TCP) and calcium pyrophosphate (CP) is synthesized in order to tailor the biodegradation behavior of the ceramic. The results show that biphasic TCP/CP ceramic has a strength of 62.2 ± 2.1 MPa, which is superior to single‐phase TCP and CP ceramics, which show strengths of 44.3 ± 3.0 and 53.0 ± 4.8 MPa, respectively. In addition, biphasic TCP/CP ceramic displays a controlled strength degradation from 62.2 ± 2.1 to 40.5 ± 1.0 MPa in sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…β‐TCP has been shown to have excellent biocompatibility, osteoconductivity, and time‐dependent biodegradation characteristics 1, 3. In many applications, the time‐dependent biodegradation properties makes β‐TCP an ideal scaffold material for bone tissue engineering, where the ceramic temporarily supports bone in‐growth, while eventually being replaced by natural tissue 4–6. The use of such bone substitute reduces the need for a possible second site surgery that is often needed for autograft harvesting 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…β‐TCP has been shown to have excellent biocompatibility, osteoconductivity, and time‐dependent biodegradation characteristics 1, 3. In many applications, the time‐dependent biodegradation properties makes β‐TCP an ideal scaffold material for bone tissue engineering, where the ceramic temporarily supports bone in‐growth, while eventually being replaced by natural tissue 4–6. The use of such bone substitute reduces the need for a possible second site surgery that is often needed for autograft harvesting 1.…”
Section: Introductionmentioning
confidence: 99%
“…1,3 In many applications, the time-dependent biodegradation properties makes b-TCP an ideal scaffold material for bone tissue engineering, where the ceramic temporarily supports bone in-growth, while eventually being replaced by natural tissue. [4][5][6] The use of such bone substitute reduces the need for a possible second site surgery that is often needed for autograft harvesting. 1 However, the in vivo strength degradation profile of pure b-TCP is not ideal for many applications in which controlled strength loss is necessary over a specific period.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium phosphates (CaPs) are widely used in bone‐tissue engineering due to their excellent bioactivity and compositional similarities to bone 1–3. Among various calcium phosphates, hydroxyapatite [HAp, Ca 10 (PO 4 ) 6 (OH) 2 ] and β‐tricalcium phosphate [β‐TCP, Ca 3 (PO 4 ) 2 ] are most commonly used because of their osteogenic property and the ability to form strong bonds with host bone tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been found that biphasic Ca phosphate is a good way to make full use of the advantages from each monophasic Ca phosphate for enhancing performances in applications [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%